Stunting Prevention: Optimizing The Family Approach With Parenting Psychoeducation - Yunia Harniati; Siti Muthia Dinni (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The role of parents is the most important thing in supervising the growth and development of children. The problem that is often experienced by children is stunting, to increase information to the public, namely through psychoeducation. The purpose of the activities carried out is to increase understanding and skills for stunting prevention through parenting. The intervention targets were pregnant women, adolescents, posyandu cadres, parents with toddlers and stunting, with a total of 34 participants. Sampling in this counseling using purposive sampling technique. Retrieval of data used is using observation, interviews, Focus Group Discussion (FGD). The methods used in psychoeducation are lecture, roleplay, and discussion methods. The results obtained from this psychoeducation show positive results, namely that the benefits of the psychoeducation given to participants are quite visible. The participants realized that after participating in the activity, the participants' information and understanding regarding stunting and parenting patterns increased, so that parenting psychoeducation could become one of the recommendations for the